"Design and Development of a Smart Mechatronic System for Waste Sorting, Shredding, and Compaction Based on Sensor Integration and Microcontroller Control" - Lianawati, Yosita; Widiastuti, Rosalina Yani; Suparno, Agus; Mikha El Charisto R; Agnes Patria W; Mikael Billyarta K (International Journal of Technology and Education Research, 2025)
This study presents the development of an automated Smart Waste Sorting, Shredding, and Compressing System to improve waste management efficiency. The system integrates capacitive and proximity sensors to classify waste into organic (leaves) and plastic categories with 100% accuracy in testing (20 plastic samples and 9 liters of organic waste accurately sorted). The shredded waste is reduced to 3 cm fragments, and subsequent compression achieves a 60% volume reduction, significantly optimizing storage and transport. The system utilizes an ESP32 microcontroller for real-time control, supported by ultrasonic sensors and servo motors for precision. Experimental results demonstrate the effectiveness of the integrated design, highlighting its potential for sustainable waste management in communities and institutions. This innovation offers a practical solution to enhance recycling processes and reduce environmental impact through automation.